PHYSICO-MORPHOLOGICAL CHARACTERS OF SEMEN OF MURRAH BUFFALO BULL - SAINI, J; DHANDE, P L; GAIKWAD, S A; SHANKHAPAL, V D; SHELAR, R R (The Indian Journal of Animal Reproduction, 2016)
The physic-morphological characters of neat semen collected using artificial vagina from sexually mature Murrah buffalo bull (n=6, age 4-6 year) was recorded. The average semen volume was 3.67±0.21 ml, milky white in colour, medium to thick consistency, pH was 6.45±0.06, average sperm concentration was 1164.17±51 million/ml, average initial motility was good (90%), average live sperm count was 83.00±2.35%, abnormal sperm count was 10.67±0.61%, 4.37±0.18 minute for methylene blue reduction test and 89.17±1.87% sperm membrane integrity. In brief, the recorded data can be useful during breeding soundness evaluation of Murrah buffalo bull.